RELIGIOUS MODERATION AS THE INITIAL EFFORT TO FORM TOLERANCE ATTITUDE OF ELEMENTARY SCHOOL - Sunarti, Sunarti; Sari, Dwivelia Aftika (AULADUNA: Jurnal Pendidikan Dasar Islam, 2021)
Abstract As social beings living in a pluralistic environment, a moderate attitude is needed to create tolerance between existing differences. It is necessary to realize the cultivation of religious moderation in education to get a moderate understanding. Religious moderation needs to be instilled not only in universities but also at the elementary school level to create student tolerance from an early age. This study aims to determine the tolerance attitude of elementary school students like what is formed by cultivating the value of religious moderation. The research types were field research and library research. The population of this study was students of SDN 010 Simpang Petai Village, with 94 students as the sample from the high class, namely grades 4, 5, and 6. The field research findings showed that the tolerance attitude of SDN 010 students in Simpang Petai Village in the peace aspect was at 30%, the respect for differences and individuals was at 25%, and the awareness aspect was at 18%. This result indicated that the tolerance attitude of students was in a bad category. Then, the field data results became a reference for conducting library research that this religious moderation was realized through character education: value inculcation, cognitive moral development, value analysis, value clarification, and learning to action approaches. In this way, student tolerance would be formed, namely religious tolerance, thought tolerance, social tolerance, and racial tolerance in elementary school students. Abstrak Sebagai makhluk sosial yang hidup di lingkungan yang majemuk maka sangat dibutuhkan sikap yang moderat agar terciptanya toleransi antar perbedaan yang ada. Untuk sampai kepada pemahaman yang moderat, maka dibutuhkan realisasi penanaman paham moderasi beragama dalam dunia pendidikan. Moderasi beragama perlu ditanamkan tidak hanya ditingkat perguruan tinggi, tapi juga sekolah dasar agar terciptanya sikap toleransi siswa dari sejak dini. Penelitian ini bertujuan untuk mengetahui sikap toleransi siswa sekolah dasar seperti apa yang terbentuk melalui penanaman nilai moderasi beragama. Jenis penelitian ini adalah penelitian lapangan (field research) dan jenis penelitian kepustakaan (library research). Adapun papulasi dari penelitian ini adalah siswa SDN 010 Desa Simpang Petai dengan sampel adalah kelas tinggi yaitu kelas 4, 5, dan 6 berjumlah 94 orang. Adapun hasil penelitian lapangan yaitu ditemukan sikap toleransi siswa SDN 010 Desa Simpang Petai pada aspek kedamaian berada di angka 30%, aspek mengahargai pebedaan dan individu berada pada angka 25% dan pada aspek kesadaran diangka 18%, hal ini menunjukkan bahwa sikap toleransi siswa berada pada kategori buruk. Hasil data lapangan menjadi acuan untuk melakukan penelitian kepustakaan bahwa moderasi beragama ini direalisasikan melalui pendidikan karakter yaitu, pendekatan penanaman nilai, pendekatan perkembangan moral kognitif, pendekatan analisis nilai, pendekatan klarifikasi nilai, dan pendekatan pembelajaran berbuat, sehingga terbentuk sikap toleransi siswa yaitu toleransi beragama, toleransi pemikiran, toleransi sosial, dan toleransi rasial pada siswa sekolah dasar.